A Case Study of the Fulbright Program in Korea - Li, Su-chun (New Dynamics in Asia, 2020)
The U.S. Fulbright Program, the flagship of international educational exchange programs in the world, was established in 1946, after the devastation of World War II. It aimed for an innovative, peaceful world. The Republic of Korea was one of the first twenty signatory countries, where the US war surplus was used to fund the bilateral academic/cultural exchanges. This article reviews the history of the US-ROK agreement, including: funding, the Board, programs, and its evolvement over the past 60 years. This research discovered some unique aspects in Korean Fulbright which adapted to the local needs for national development.